Work and leisure: daily perceptions of people with physical disabilities (Research, Society and Development, 2020)
The research aims to verify the perception of workers with physical disabilities in their day-to-day work and in their days off and leisure, seeks to understand how people in different age groups and different work activities and in medium and large, face disabilities and daily challenges to work and play. It seeks to understand concepts of inclusion and accessibility. A parallel was made with the existing legislation, international treaties that protect people with disabilities, created to promote the rights of people with disabilities, existing studies on the subject and the experiences described by the people interviewed. Faced with so many challenges faced by people with physical disabilities, the main point of the interviewees was the architectural barriers, as well as lack of respect for the special spaces reserved in parking lots and the desire that the culture of respect for the other and individualities will be a reality for the day. disabled person.